Compact thirteen‐band antenna for 4G/5G/WLAN metal frame mobile phones. Issue 3 (9th December 2019) - Huang, Daiwei; Du, Zhengwei; Wang, Yan
Abstract: An antenna which can cover 13 bands for 4G/5G/WLAN mobile phones including metal frames and has the size of 70 mm × 7 mm × 7 mm is proposed and studied. It comprises four ground branches and a coupled line. The merit of the antenna proposed in this article is that it can cover 13 bands under the condition of a metal frame environment and a 7 mm ground clearance. The prototype of the proposed antenna is fabricated and tested. The measured impedance bandwidths (reflection coefficient less than −6 dB) are 315 MHz (0.680‐0.995 GHz), 1.1 GHz (1.67‐2.77 GHz), 0.65 GHz (3.25‐3.9 GHz), and 1.35 GHz (4.55‐5.9 GHz). The LTE700, LTE2300, LTE2500, UMTS, GSM850, GSM900, GSM1800, and GSM1900 bands for 4G/3G/2G systems, the 3.5 GHz and 4.8 GHz bands for 5G system, and the 2.4 GHz, 5.2 GHz and 5.8 GHz bands for the WLAN system are covered. The measured efficiencies and patterns are also presented.